Correlation Ki67 Expression With peritumoral budding Tumor Index In the Case of Squamous Cell Carcinoma Cervix NOS And Adenocarcinoma Cervix NOS - Wardini, Indah Astri; Alferraly, T. Ibnu; Chrestela, Jessy; Betty, Betty; Intan, T. Kemala; Lubis, H. M. Nadjib Dahlan (Majalah Patologi Indonesia, 2024)
Background Cervical cancer is a neoplasm in the cervix due to abnormal cells that damage the surrounding tissue. Cervical cancer from squamous cells is called squamous cell carcinoma cervix NOS and that from glands is called adenocarcinoma cervix NOS. The prognostic of both can be assessed by tumor budding and Ki67 immunohistochemistry, tumor budding is a tumor bud which is ≤ 5 cells in a cluster that grows in front of the parent tumor and immunohistochemistry Ki67 is a labile nonhistone nuclear protein which is expressed in the G1, S, G2 and M phases of the cycle cell.   Method This research is an analytical type of research that aims to find out the relationship between Ki67 expression and the peritumoral budding tumor index compared to cases of squamous cell carcinoma cervix NOS and adenocarcinoma cervix NOS with 36 paraffin block samples diagnosed with squamous cell carcinoma NOS and adenocarcinoma NOS at HAM Hospital. Medan. Assessment method of Ki67 expression where low expression (<20%) and high expression (≥20%). Assessment of peritumoral budding tumors in both cases was said to be low buds if < 5 buds and high buds if ≥ 5 buds. Results This study provides a significant appearance (p-value 0.0001) which means that peritumoral budding tumors with HE staining can be accepted as a measuring tool for assessing cervical cancer in addition to assessment using immunohistochemistry Ki67 which is generally used in the prognostic assessment of cervical cancer. Conclusion Assessment in this case can consider peritumoral budding tumor assessment to determine prognostic in cases of squamous cell carcinoma NOS and cervical adenocarcinoma NOS, if Ki67 immunohistochemistry is not available.